Gauge Object Oriented Programming in Student’s Learning Performance, Normalized Learning Gains and Perceived Motivation with Serious Games - Suhni Abbasi; Hameedullah Kazi; Ahmed Waliullah Kazi; Kamran Khowaja; Ahsanullah Baloch (Information, 2021)
Serious Games (SG) provide a comfortable learning environment and are productive for various disciplines ranging from Science, Technology, Engineering, and Mathematics (STEM) to computer programming. The Object Oriented (OO) paradigm includes objects related to real life, and is considered a natural domain that can be worked with. Nonetheless, mapping those real-life objects with basic Object-Oriented Programming (OOP) concepts becomes a challenge for students to understand. Therefore, this study is concerned with designing and developing an SG prototype to overcome students’ difficulties and misconceptions in learning OOP and achieving positive learning outcomes. An experimental evaluation was carried out to show the difference between the experimental group students’ performance, who interact with the developed game, and students of the control group, who learn via the traditional instructional method. The experimental evaluations’ main finding is that the experimental group’s performance is better than the control group. The experimental group’s Normalized Learning Gain (NLG) is significantly higher than the control group (p < 0.005, pairedt-test). The evaluation study results show that the developed prototype’s perceived motivation on the Instructional Materials Motivation Survey (IMMS) 5-point Likert scale resulted in the highest mean score for attention (3.87) followed by relevance (3.66) subcategories. The results of this study show that the developed SG prototype is an effective tool in education, which improves learning outcomes and it has the potential to motivate students to learn OOP.